2008
DOI: 10.1002/adsc.200800472
|View full text |Cite
|
Sign up to set email alerts
|

Palladium on Calcium Carbonate Combined to 2‐Hydroxypropyl‐α/β‐cyclodextrins: A Selective Catalytic System for Aqueous Heck Coupling and Hydroarylation

Abstract: An efficient, selective and recoverable catalytic system for ligand-free aqueous Heck reactions using hydroxypropylated cyclodextrins (HPCDs) and palladium on calcium carbonate (Pd/CaCO 3 ) is highlighted. Remarkably, stereo-and chemoselectivities could be tuned by the cavity size of cyclodextrins, exploiting the relevance of host-guest interactions. UVVis experiments have led to strong evidence concerning an interplay between Pd(II) and a-HPCD, possibly ascribed to a reduction/stabilization effect of CDs. Une… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…These results indicated that the cyclodextrins could act as a protecting layer of the palladium particles and so allowed to keep moderate size. Such behavior has been previously observed in the case of metallic ruthenium nanoparticles [28,29] and in C-C cross-coupling reactions in aqueous media, including Heck, Suzuki and Sonogashira reactions, while using Pd nanoparticles stabilized by 2-hydroxypropyl-a-cyclodextrin [13]. Since cyclodextrins avoided sintering of palladium particles, together with an important concentration, the catalytic activity is higher compared to the reaction in the absence of cyclodextrins.…”
Section: Study Of the Stability Of The Catalytic Systemmentioning
confidence: 62%
See 1 more Smart Citation
“…These results indicated that the cyclodextrins could act as a protecting layer of the palladium particles and so allowed to keep moderate size. Such behavior has been previously observed in the case of metallic ruthenium nanoparticles [28,29] and in C-C cross-coupling reactions in aqueous media, including Heck, Suzuki and Sonogashira reactions, while using Pd nanoparticles stabilized by 2-hydroxypropyl-a-cyclodextrin [13]. Since cyclodextrins avoided sintering of palladium particles, together with an important concentration, the catalytic activity is higher compared to the reaction in the absence of cyclodextrins.…”
Section: Study Of the Stability Of The Catalytic Systemmentioning
confidence: 62%
“…However, the exclusive use of water often leads to modest yields and the use of phase transfer agent additives like tetraalkylammonium salts are essential in order to circumvent such limitation [9,10]. Recently, the effect of cyclodextrins as phase-transfer agent on the C-C cross-coupling reaction in water was demonstrated [11][12][13][14][15][16]. Moreover, the beneficial effect of the presence of cyclodextrins on the selective preparation of cinnamaldehyde and aryl propionic ester using Pd salts in aqueous phase was reported [17].…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, CD derivatives have commonly been applied successfully in various organic reactions, especial involving green chemistry. Among these, CDs have attracted a wide interest in the synthesis and stabilization of transition metal nanoparticles for carbon–carbon bond formation . Furthermore, Matt et al showed that cavity‐shaped ligands could bring an added value to the efficiency of Suzuki–Miyaura coupling .…”
Section: Resultsmentioning
confidence: 99%
“…It was assumed that hydroxylpropylated CD increased the dispersion of the Pd/BaCO 3 and stabilized Pd clusters leached from the support. In fact, the heterogeneous Pd/BaCO 3 solid could act as a reservoir of catalytically active Pd species [109,110].…”
Section: Dispersion and Activation Of Palladium Charcoal By Cyclodextmentioning
confidence: 99%